Analisis material untuk rancangan Kartu Karuta bertema sejarah desain produk - Widyastuti, Putri Anggraeni; Zahar, Iwan; Pertiwi, Ratih; Susanto, Ratnawati (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
History is not a subject that is understood by students in the field of design at the beginning of the lecture. Generally, students in the field of product design have problems in understanding the history of product design as a basis for product design. The karuta card game was chosen to overcome this problem. The next obstacle is choosing the appropriate material in the development of a product design history-themed card design. The benefits and objectives of this research are to produce data that can be used in designing similar products. The method used in solving this problem is material benchmarking analysis. This is used to generate data that can be used in the development of Karuta card designs with the theme of Product Design History.From comparing several karuta game products sold at Okunokaruta stores in Tokyo Japan and Daiso, and used by the Ogura Karuta Club community at Dharma Persada University through benchmarking analysis, it can be seen from the dimensions of the product, the type of material, the gram weight of the paper, and durability. The result is the type of material that will be used. In conclusion, from the results of the benchmarking analysis, the paper material used in the development of the karuta game design with the theme of product design history is at least 300gsm with a minimum thickness of about 0.32 mm or 0.35 mm made of plastic coated paperboard, and measuring about 5.4 cm x 7.4 cm to 7.2 cm x 5 cm.